High-temperature stable field emission of B-doped SiC nanoneedle arrays. Issue 17 (15th April 2015) - Wang, Lin; Wei, Guodong; Gao, Fengmei; Li, Chengming; Yang, Weiyou
Abstract : We report the field emission of B-doped SiC nanoarrays, suggesting they could be robust electron sources for service under high temperatures. Abstract : Current emission stability is one of the key issues for field emitters for them to be practically applied as electron sources. In the present work, large-scale and well-aligned B-doped SiC nanoneedle arrays have been grown on 6 H -SiC wafer substrates via pyrolysis of polymeric precursors. The measured field emission (FE) characteristics suggest that the turn-on fields of the as-synthesized SiC nanoneedle arrays are reduced from 1.92 to 0.98 V μm −1 with temperature increasing from room temperature (RT) to 500 °C, suggesting their excellent FE performances. The slightly changed current fluctuations (only ∼1.3%) between RT and 200 °C confirm that the present SiC nanoarrays with B dopants could be highly stable field emitters to be used in service under harsh conditions of high temperatures.